PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MEDIA PEMBELAJARAN ULAR TANGGA PADA MATA PELAJARAN IPAS KELAS III SD NEGERI 1 SUKAMULIA - Amalya Garnis, Aizyra; Kudsiah, Musabihatul; Atsarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low levels of student participation and learning outcomes in the Natural and Social Sciences (IPAS) subject among third-grade students at SD Negeri 1 Sukamulia. This condition was caused by teacher-centered learning practices, which limited students' active involvement in the learning process. The study aimed to improve students' participation and learning outcomes through the implementation of snakes and ladders learning media in IPAS instruction. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The participants were 23 third-grade students of SD Negeri 1 Sukamulia. Data were collected through observation, tests, and documentation, and were analyzed using quantitative and qualitative descriptive techniques. The results showed that student participation increased from 47.8% in the pre-cycle stage to 71.7% in Cycle I and 89.1% in Cycle II. The average learning outcome score increased from 63.7 to 72.8 and reached 82.4, while classical learning mastery improved from 39.1% to 69.6% and finally reached 87.0% in Cycle II, indicating that the predetermined success indicators had been achieved. Based on these findings, it can be concluded that the implementation of snakes and ladders learning media was effective in improving student participation and learning outcomes in the IPAS subject for third-grade students at SD Negeri 1 Sukamulia.